ADOLESCENT GIRLS’ WILLINGNESS TO DISCLOSE SEXUAL ABUSE THROUGH INTERPERSONAL COMMUNICATION IN DELTA-CENTRAL SENATORIAL DISTRICT OF DELTA STATE - Odedede, Joan N.; Uzochukwu, Chinwe E. (African Journal of Social and Behavioural Sciences, 2025)
Sexual abuse remains a critical social issue, particularly among adolescent girls who face barriers in telling their sexual abuse experiences. The study examines the willingness of adolescent girls to talk about sexual abuse experience through interpersonal communication in Delta Central Senatorial District of Delta State. The study explores the factors that influence willingness to tell abuse experiences by fostering empathy, trust, understanding, and privacy assurance and providing a safe environment for in-person interactions. Using the mixed method research design. The qualitative and quantitative approaches utilised the interview and survey to elicit data from the adolescent girls. Findings revealed that interpersonal relationship could promote conversational willingness through asking children and adolescents their sexual experiences can help facilitates telling with a grand mean of 3.8749 and 1.1057 3) Findings also revealed that empathy could help sexually abuse victims disclose experiences (Mean = 3.9687) and having strong parent-child relationship influences a decision to disclose abuse experiences? (Mean = 3.9531) with a grand mean and standard deviation of 3.8869 and 1.1015. More so, the results obtained from the IDI support the above assertion that believing in their story and not blaming them encouraged them to tell me about the sexual abuse. The study underpins that interpersonal communication can provide conversational willingness among sexually abused adolescent girls.